Protection of Grouper Against Cryptocaryon irritans by Immunization With Tetrahymena thermophila and Protective Cross-Reactive Antigen Identification - Mo, Zequan; Wu, Huicheng; Hu, Yingtong; Lai, Xueli; Guo, Wenjie; Duan, Yafei; Dan, Xueming; Li, Yanwei (Frontiers in immunology, 2022)
Vaccination is an effective method to prevent Cryptocaryon irritans infection. Although some vaccines have been developed, large-scale production of these vaccines is costly. Development of a heterogenous vaccine generated by low-cost antigens is an alternative method. In the present study, grouper immunized with Tetrahymena thermophila , a free-living ciliate that easily grows in inexpensive culture media at high density, showed protective immunity against C. irritans infection. Higher immobilization against C. irritans theronts was detected in T. thermophila –immunized grouper serum, which suggested the existence of a cross-reactive antibody in the serum. By immunoprecipitation and mass spectrometry analyses, tubulin was identified as a potential cross-reactive antigen between C. irritans and T. thermophila . Recombinant T. thermophila tubulin protein (rTt-tubulin) and its antibody were prepared, and immunofluorescence showed that both C. irritans and T. thermophila cilia were stained by the anti–rTt-tubulin antibody. Grouper immunized with rTt-tubulin showed a reduced infective rate after the C. irritans challenge. An enhanced level of C. irritans –binding immunoglobulin M (IgM) antibody was detected in serum from rTt-tubulin–immunized grouper. Moreover, specific antibodies were also found in the mucus and tissue culture medium from rTt-tubulin–immunized grouper. Overall, these findings suggested that vaccination with T. thermophila elicits cross-reactive protective immunity in grouper against C. irritans , and T. thermophila may be a potential heterologous antigen for vaccine development.